Aplikasi Nilai-nilai Kristiani dalam Keluarga di Era Digital - Yuni Setiani Merlianta Girsang; Intansakti Pius X (International Forum of Researchers and Lecturers, 2024)
Family is an intact fellowship or community based on intimate love that occurs between husband and wife and children in building a happy family. Especially in doing faith education for children's faith development, especially in today's digital era. The digital era brings various changes in human life, including in family dynamics. The application of Christian values in families in the digital era is very important to be applied in daily life. Christian values such as love, patience, joy and peace, gentleness, open communication, mutual respect, and forgiveness can be the foundation for everyone in building a strong and resilient family in facing the challenges of the digital era and educating children to apply Christian values in daily life to face the increasingly sophisticated and rapid technological developments wisely.